P186 Facilitators to recruiting COPD patients to an adherence intervention trial. (11th November 2022) - Dickens, AP; Halpin, DMG; Carter, V; Skinner, D; Beeh, K; Chalmers, J; Clark, A; Hannan, N; Kaplan, A; Kostikas, K; Pinnock, H; Roche, N; et al.
Abstract : Introduction and Objectives: Recruitment rates to clinical trials in primary care are often lower than anticipated, even in successful trials. Researchers can be too optimistic about the number of eligible patients, and the GPs' time and ability to recruit patients. The MAGNIFY cluster randomised trial is investigating the effect of a technologically-supported adherence package (Ultibro Breezhaler + adherence support technology) for COPD patients in primary care. This abstract explores facilitators for recruiting patients into a GP practice-level intervention trial. Methods: Eligible practices willing to implement the adherence package were invited to participate. Algorithms run on electronic medical records (EMR) of intervention arm practices identified COPD patients aged ≥40 years, with ≥2 moderate/severe exacerbations in the last two years and ≤50% adherence to mono/dual therapy. Pharmacists were funded to recruit patients over a maximum of two calls; initial calls entailed a remote review and invitation to use the technology if suitable, with offer of a second to support device set-up and resolve problems. Results: To date, 398/672 (59.2%) potentially eligible patients have been reviewed. 67/398 (16.8%) were deemed clinically unsuitable during the initial call. Of the remaining 331 patients, 218 (96.1%) accepted the support package; giving an overall recruitment rate onto the intervention of 54.8% (218/398 patients). Conclusions: The recruitment rate was higher than many primary care trials. Recruitment of primary care patients into intervention trials may benefit from using cluster randomised trial designs and adopting novel approaches including EMR searches and dedicated pharmacists to identify, screen and recruit potential patients.